Pelatihan Perbanyakan Mikroorganisme pada Kelompok Tani di Distrik Semangga Kabupaten Merauke - Sarijan, Abdullah; Untari, Untari; Melmambessy, Edy H.P; Simatupang, David Oscar; Adrianus, Adrianus; Yusuf, Mega Ayu; Anwar, Anwar; Kurniawan, Ade; Sembiring, Jefri; Yusuf, Mani; Samosir, Hasianna Darmawati (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
This community service activity aimed to improve the knowledge and skills of farmer groups in Semangga District, Merauke Regency in propagating microorganisms as biological agents in agriculture. The program was motivated by farmers’ high dependence on chemical fertilizers and pesticides, which negatively affect soil quality and the environment. The methods included laboratory-based microorganism propagation, interactive lectures, simulation practices, and group discussions and reflections. The results indicated increased farmers’ understanding of the roles and benefits of microorganisms such as Trichoderma sp. and Bacillus sp., as well as their ability to propagate them independently. The application of this technology has the potential to reduce chemical inputs, lower production costs, and improve soil fertility sustainably. This activity is important as a model for empowering farmers through environmentally friendly biological technology.